(untitled) (Al-Academy, 2017)
represent websites link support of human communicate and cohesion of cultures different depending on their languages and their environments around, it was the evolution of one of the most important means of communication of services for electronic networks, the Internet active role in containing the world Bbodqh science and knowledge to Taatlaqah cultures from which derives its intellectual and cognitive cupboards continuity and as a link language for each those environmental Altdadat, linguistic, religious, political, economic . We all know that these electronic means difficult promise ring intellectual and mental connectivity for the masses polarized without being of the image as an element Kravekaa supporter of the electronic media and which ones achieved connection as it is the simplicity of formality earn Arafatha a product of context, organizer of the offer to store memory in accordance with the environmental and intellectual Layout and knowledge to confer upon the global recipe from which we derive knowledge of what goes on around us to make a difficult arrival or misunderstood by other means communication. this mix communication is one of the one of the most important in the communication process structural elements for the intervention of the image within the mix to be an element Kravekaa supporter in the translation of cultures and the dissemination of knowledge and awareness and which ones identified the following research problem by asking:- What are the implications of the theory of knowledge on the press image in designs websites?The aim of the research was stationed in identifying and Implications for the image and role of the press the Communicative in web design theory of knowledge.And resulted in the conclusions that resulted from the current research: – The epistemology her active role in the translation of the shapes phenomenon of the image to turn it into a Perception Aflah paint forms moot third phenomenon that rely primarily on advanced symbolic order and the perceived thing.- reflections of the theory of knowledge to draw the visual perceptions and reasoning to identify and stimulate the overall sensory effervescence to interact with the event and activating the idea